Characterization of osseointegrative phosphatidylserine and cholesterol orthopaedic implant coatings - Rodgers, William Paul, author; James, Susan, advisor; Popat, Ketul, committee member; Ehrhart, Nicole, committee member; De Long, Susan, committee member (Colorado State University. Libraries, 2013)
Total joint arthroplasties/replacements are one of the most successful surgeries available today for improving patients’ quality of life. By 2030 in the US, demand for primary total hip and knee arthroplasties are expected to grow by 174% and 673% respectively to a combined total of over 4 million procedures performed annually, driven largely by an ageing population and an increased occurrence of obesity. Current patient options for load-bearing bone integrating implants have significant shortcomings. Nearly a third of patients require a revision surgery before the implant is 15 years old, and those who have revision surgeries are at an increased risk of requiring additional reoperations. A recent implant technology that has shown to be effective at improving bone to implant integration is the use of phosphatidylserine (DOPS) coatings. These coatings are challenging to analyze and measure due to their highly dynamic, soft, rough, thick, and optically diffractive properties. Previous work had difficulty investigating pertinent parameters for these coating’s development due in large part to a lack of available analytical techniques and a dearth of understanding of the micro- and nano-structural configuration of the coatings. This work addresses the lack of techniques available for use with DOPS coatings through the development of original methods of measurement, including the use of scanning white light interferometry and nanoindentation. These techniques were then applied for the characterization of DOPS coatings and the study of effects from several factors: 1. the influence of adding calcium and cholesterol to the coatings, 2. the effect of composition and roughness on aqueous contact angles, and 3. the impact of ageing and storage environment on the coatings. This project lays a foundation for the continued development and improvement of DOPS coatings, which have the promise of significantly improving current patient options for bone integrating implants. Using these newly developed and highly repeatable quantitative analysis methods, this study sheds light on the microstructural configuration of the DOPS coatings and elucidates previously unexplained phenomena of the coatings. Cholesterol was found to supersaturate in the coatings at high concentration and phase separate into an anhydrous crystalline form, while lower concentrations were found to significantly harden the coatings. Morphological and microstructural changes were detected in the coatings over the course of as little as two weeks that were dependent on the storage environment. The results and understanding gained pave the path for focused future research effort. Additionally, the methods and techniques developed for the analysis of DOPS coatings have a broader application for the measurement and analysis of other problematic biological materials and surfaces.
Keywords: biomaterials; nanoindentation; orthopaedic implants; osseointegration; scanning white light interferometry; surface analysis